Suara Kosong pada Pilkada Serentak di Indonesia: Perspektif Hukum Tata Negara Islam - Mangar, Irma; Tahe , Nur-amimi; Ridho , Muhammad Rosyid; Asri Elies, Asri Elies; Sudrajat, Shinta Azzahra; Luluardi, Yunas (Jurnal Hukum Islam, 2024)
The increasing number of single candidates and blank votes in the simultaneous regional elections is a fact in the democratic process in Indonesia. This paper discusses blank votes in simultaneous regional elections, which are a dilemma in enforcing the principles of democracy. Furthermore, it discusses blank votes from the perspective of Islamic constitutional law. The research method uses normative juridical with a statutory, conceptual and case approach. The results show that the fact of single candidates in the simultaneous regional elections which are legitimized by laws and regulations opens up the opportunity for blank votes to emerge which are "deemed" as a solution in the democratic process in the regions. The author argues that the single candidates and blank votes in the simultaneous regional elections are a dilemma in realizing the principles of democracy. On the one hand, the principles of democracy must be upheld as mandated by the constitution, but on the other hand, the regional election process must continue even with only a single candidate. Islam offers principles in the implementation of state administration, namely prioritizing syura (deliberation), fairness, not siding with the wrong and prioritizing equality. Al-Mawardi emphasized that political practices in the election of state leaders require religion as a moral force, charismatic leaders and justice for all people. That idea is relevant to the principles of democracy in Indonesia, where religion, humanity, unity, deliberation and justice are its basis. This study is expected to be a reflection material to realize a more democratic election.